Variability of sleep bruxism: findings from consecutive nights of monitoring - Ohlmann, Brigitte; Bömicke, Wolfgang; Behnisch, Rouven; Rammelsberg, Peter; Schmitter, Marc (Clinical oral investigations, 2022)
Objectives  To determine sleep bruxism (SB) behavior during five consecutive nights and to identify correlations between SB episodes per hour (SB index) and sleep-time masseter-muscle activity (sMMA). Material and methods  Thirty-one participants were included in the study. Of these, 10 were classified as sleep bruxers (group SB-1) and nine as non-sleep bruxers (group non-SB). The bruxism status of these 19 patients was identified by means of questionnaires, an assessment of clinical symptoms, and electromyographic/electrocardiographic data (Bruxoff® device). The remaining 12 participants were also identified as bruxers, but based exclusively on data from the Bruxoff device (group SB-2). Data analysis included descriptive statistics and Spearman’s correlation to assess the relationship between the SB index and sMMA. - Results  Participants in group SB-1 showed an overall mean SB index of 3.1 ± 1.6 and a mean total sMMA per night of 62.9 ± 38.3. Participants in group SB-2 had an overall mean SB index of 2.7 ± 1.5 and a mean total sMMA of 56.0 ± 29.3. In the non-SB group, participants showed an overall mean SB index of 0.8 ± 0.5 and a mean total sMMA of 56.8 ± 30.3. Spearman’s correlation yielded values of − 0.27 to 0.71 for the correlation between sMMA and SB index. - Conclusions  The data revealed variable SB activity and the absence of a reliable correlation between sMMA and the SB index. Clinical relevance  The high variation in SB activity and lack of correlation between sMMA and the SB index should be considered when diagnosing SB. Trial registration  Clinical Trials [NIH], clinical trial no. NCT03039985.